Morbidity pattern and health-seeking behaviour among the senior citizens in a selected urban area of Bangladesh: A cross-sectional study - Gupta, Rajat Das; Loha, Avijit; Roy, Saikat (South East Asia Journal of Public Health, 2016)
Elderly people suffer from different morbidities as the increase in prevalence of disease is proportionate to increasing age. In Bangladesh, the number of the elderly person is increasing with time. This study aims to determine the morbidity pattern and health seeking behavior among the urban senior citizens of Bangladesh. A cross-sectional study was carried out from January 2014 to December 2014 in different areas of Dhaka City. Information was collected from 384 respondents, aged 60 years and above by purposive sampling technique. The mean age of the study population was 64.7 (SD±5.7) years and majority (74.74%) belonged to 60-69 years age group. More than half (52.6%) of the respondents were female. Most of the respondents (71.61%) received institutional education; 51.82% of the elderly were still working; 63% of the respondents were totally independent; 11.74% were totally dependent; and 53.65% respondents belonged to joint family. Most of the respondents (96.8%) were suffering from at least one medical problem; the commonest was musculoskeletal problems (84.11%) followed by eye problems (81.25%). Majority of male (78.8%) and females (89.60%) were suffering from eye problems and musculoskeletal problems respectively. All the respondents sought treatment for their health problems. Majority (33%) respondents went to government hospitals for medical help. Most of the male (68.70%) and female (71.26%) can do their daily physical activities without any problem. Approximately 30% respondents did health check-up once in one year. Majority respondents took prescribed medications (69.27%) and were satisfied with their treatment (56.77%). The study findings showed that urban geriatric population had one or more morbidities and their health seeking behavior was poor, more among females. The study concludes with further emphasis of primary health care for the urban elderly people of Bangladesh. The health care service should be accessible and affordable to the elderly people. South East Asia Journal of Public Health Vol.5(2) 2015: 43-49